INTERMITTENT WORK: ITS CONSEQUENCES FOR THE SECURITY AND ECONOMIC STABILITY OF BRAZILIAN EMPLOYEES (CIPEEX, 2025)
The intermittent employment contract is yet another way for employers to keep employees waiting. This period is usually seasonal, i.e. in times of high demand, the manager looks for employees to fill deficits in the company without any employment relationship with them. It is worth noting that this type of work violates employee rights in their most degraded form. This work is therefore justified by the need to discuss the labor reform from an enlightening perspective based on legal provisions and real data from the current economic scenario, taking into account the intermittent employment contract. The general objective was to analyze whether there is room in the legal system for the constitutionality of an institute such as the intermittent employment contract. The specific objectives were to define intermittent work and its position in labor legislation; to verify whether intermittent work is safe for the employee's well-being in terms of continuity at work; to identify the advantages and disadvantages of intermittent contracts and their impact on working hours. The methodology consisted of a literature review with a qualitative approach. The research used the hypothetical-deductive method, with interpretation of the normative text and ex post facto. The comparative method was also used to promote public discussion related to the proposal to standardize case law, which impacts everyone subject to the CLT. In the end, it was concluded that it is important to have clear and precise regulation of intermittent work in order to avoid abuses and guarantee the protection of employees, based on constitutional principles.
Keywords: intermittent employment contract; constitutionality; unconstitutionality